2022
DOI: 10.1097/mcg.0000000000001736
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel 1-year Mortality Risk Score That Includes the Use of Antithrombotic in Patients With Overt Gastrointestinal Bleeding

Abstract: Goals and Background: We aimed to develop a novel 1-year mortality risk-scoring system that includes use of antithrombotic (AT) drugs and to validate it against other scoring systems in patients with acute gastrointestinal bleeding (GIB). Study: We developed a risk-scoring system from prospectively collected data on patients admitted with GIB between January 2013 and August 2020, who had at least 1- year of follow-up. Independent predictors of 1-year mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The studies on non-variceal UGIB showed inconsistent results [ 22 ]. Our study, which included patients with UGIB, LGIB and only a small proportion of patients with variceal hemorrhage, found that BT did not affect long-term mortality, but increased 1-year mortality 3-fold, even after adjustment for confounders [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies on non-variceal UGIB showed inconsistent results [ 22 ]. Our study, which included patients with UGIB, LGIB and only a small proportion of patients with variceal hemorrhage, found that BT did not affect long-term mortality, but increased 1-year mortality 3-fold, even after adjustment for confounders [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies were limited by the fact that transfused patients are generally sicker than non-transfused ones, 2 recent studies that used propensity matching to compare transfused and non-transfused patients suggested that BT does indeed increase the risk of mortality and rebleeding [ 9 , 10 ]. Furthermore, in a prospective study of patients presenting with GIB, BT was found to be an independent predictor of 1-year mortality [ 11 ].…”
Section: Introductionmentioning
confidence: 99%